Non-canonical Inflammasome-Mediated IL-1β Production by Primary Endometrial Epithelial and Stromal Fibroblast Cells Is NLRP3 and Caspase-4 Dependent - Kelly, Paul; Meade, Kieran G.; O'Farrelly, Cliona (Frontiers in Immunology, 2019)
Inflammation of the postpartum uterus is a normal physiological event, crucial for tissue involution and repair. However, in the bovine, some cows fail to resolve this inflammation, resulting in endometritis, which compromises fertility. Here we hypothesize that inflammasome-mediated cleavage of the inflammatory cytokine IL-1β in the uterus is a key driver of pathological inflammation in endometritic cows. Endometrial tissue samples were obtained at 7 and 21 days post-partum (DPP) from cows that developed endometritis at 21 DPP and cows that remained healthy throughout involution. IL-1β was measured by qPCR, ELISA and immunohistochemistry. Seven DPP, endometrial IL-1β protein levels were significantly higher in animals that proceeded to develop endometritis at 21 DPP with production by the epithelium (both luminal and glandular), underlying stromal fibroblasts as well as infiltrating immune cells. Stimulation of primary endometrial epithelial cells, stromal fibroblasts and PBMCs with LPS and the inflammasome activator nigericin induced high levels of IL-1β. Stromal fibroblast cells were particularly potent producers of IL-1β. Furthermore, basolateral LPS stimulation of polarized epithelial cells induced IL1B mRNA and a previously undescribed IL-1β protein isoform, with preferential protein secretion into the apical compartment. Key inflammasome components (NLRP3, NEK7, ASC and Gasdermin-D) were expressed by endometrial cells following stimulation. Endometrial cell stimulation in the presence of NLRP3 receptor (MCC950) and pan-caspase (Z-VAD-FMK) inhibitors blocked IL-1β production, demonstrating its dependence on the NLRP3 inflammasome and on caspase activity. Interestingly, in contrast to inflammasome pathways detected in other species, expression of caspase-4 but not caspase-1 was detected in bovine endometrial cells. Caspase-4 specific siRNA prevented IL-1β production, confirming that inflammasome activation in endometrial cells is caspase-4 but not caspase-1 dependent. This study has identified species- and tissue-specific differences in bovine endometrial cell inflammasome assembly. Identifying the mechanisms of inflammasome activation operating in the bovine has critical relevance for our understanding of inflammation and suggests new therapeutic targets for the resolution of inflammatory pathologies in the bovine and in particular for the prevention of bovine endometritis.